In Defense of Deliberative Indispensability. (22nd February 2021) - Lutz, Matt
Abstract: David Enoch has argued that we can be justified in believing in irreducibly normative reasons on the grounds that such reasons are deliberatively indispensable. This deliberative indispensability argument has been attacked from a variety of angles and is generally held to be rather weak. In this paper, I argue that existing criticisms of the deliberative indispensability argument do not touch the core of Enoch's argument. Properly understood, the deliberative indispensability argument is much stronger than its critics allege. It deserves to be taken seriously.